The allocation system of the elementary school building construction program in Leyte - Macato, Leonor C. (Leyte-Samar Studies, 1987)
When people organize formally to attain a common goal, it is essential that there be management-the task of creating the internal environment for organized effort to accomplish group goals. In this study, the respondents are involved in the management of allocating the financial resources of the public elementary school building construction programs in the province of Leyte. The main objective is to provide the elementary schools of the province sufficient classrooms that are in good physical condition.